2010
DOI: 10.1158/0008-5472.can-09-2544
|View full text |Cite
|
Sign up to set email alerts
|

Essential Requirement for PP2A Inhibition by the Oncogenic Receptor c-KIT Suggests PP2A Reactivation as a Strategy to Treat c-KIT+ Cancers

Abstract: Oncogenic mutations of the receptor tyrosine kinase c-KIT play an important role in the pathogenesis of gastrointestinal stromal tumors, systemic mastocytosis, and some acute myeloid leukemias (AML). Although juxtamembrane mutations commonly detected in gastrointestinal stromal tumor are sensitive to tyrosine kinase inhibitors, the kinase domain mutations frequently encountered in systemic mastocytosis and AML confer resistance and are largely unresponsive to targeted inhibition by the existing agent imatinib.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
156
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(164 citation statements)
references
References 46 publications
6
156
2
Order By: Relevance
“…18 Pharmacological activation of PP2A has been suggested as a promising strategy to treat c-KITC cancers. 19 Despite these anticancer effects, PP2A may play a tumor-promoting role in some settings. For instance, targeting PP2A via antisense technology results in decreased proliferation of human multiple myeloma cells.…”
Section: Discussionmentioning
confidence: 99%
“…18 Pharmacological activation of PP2A has been suggested as a promising strategy to treat c-KITC cancers. 19 Despite these anticancer effects, PP2A may play a tumor-promoting role in some settings. For instance, targeting PP2A via antisense technology results in decreased proliferation of human multiple myeloma cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that impaired PP2A activity has a key role in BCR/ABL-positive leukemias, such as CML and acute lymphoblastic leukemia, 31,32 in myeloid precursors expressing imatinib-sensitive (V560G) and imatinib-resistant (D816 V) mutant c-KIT, 36 and also in chronic lymphocytic leukemia; 46 moreover, activation of PP2A by either FTY720 or forskolin seems to have promising therapeutic effects in these diseases. Abbreviation: AML, acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…10 As indicated above, only few studies have reported reduced PP2A activity in AML. 35,36 Our group has recently reported an impaired PP2A activity by SET as a consequence of SETBP1 overexpression, a recurrent event in AML (27%). 37 This leads us to hypothesize that PP2A inhibition could be a recurrent event in AML.…”
Section: Pp2a Inhibition In Aml I Cristóbal Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…For example, FTY720 interacts with the cannabinoid family of GPCRs (77), but the primary cannabinoid receptors, CB 1 and CB 2 , are not involved in the EC barrier-enhancing response (70). In addition, FTY720 (but not S1P) inhibits S1PL (78), cytosolic phospholipase A 2 (79), and ceramide synthases (80,81), and activates protein phosphatase 2A (82). In human lung ECs, FTY720 increased c-Abelson tyrosine kinase (c-Abl) tyrosine kinase activity, and c-Abl siRNA attenuated FTY720-dependent barrier enhancement ( Figure 5) (83).…”
Section: Mechanisms Of Barrier Regulation By Fty720 and Fty720-pmentioning
confidence: 99%